The Proinflammatory Role of Guanylate-Binding Protein 5 in Inflammatory Bowel Diseases - Li, Yichen; Lin, Xutao; Wang, Wenxia; Wang, Wenyu; Cheng, Sijing; Huang, Yibo; Zou, Yifeng; Ke, Jia; Zhu, Lixin (Frontiers in Microbiology, 2022)
NLRP3 inflammasome is implicated in the pathogenesis of inflammatory bowel diseases (IBD). Since guanylate-binding protein 5 (GBP5) induces the NLRP3 inflammasome activity, we aim to investigate the potential role of GBP5 in IBD pathogenesis. The expression of GBP5, NLRP3 inflammasome, and related cytokines and chemokines was examined in two cohorts of IBD patients and healthy controls, by microarray transcriptome analysis and quantitative real-time PCR. Cellular localization of GBP5 in colonic biopsies was examined by immunohistochemistry and immunofluorescence with confocal microscopy. For functional studies, GBP5 was induced by interferon γ or silenced by siRNA or CRISPR/CAS9 technique, and inflammatory activities were evaluated at mRNA and protein levels. We found that the expression of GBP5 was elevated in colonic mucosa in two geographically and culturally distinct IBD cohorts. In colonic tissues of IBD patients, GBP5 expression was mainly confined to immune cells and the levels of GBP5 expression were correlated with those of the inflammatory cytokines and chemokines. In cultured T and macrophage cells, the expression of proinflammatory cytokines and chemokines was increased when GBP5 was induced, while GBP5 deficiency leads to decreased expression of proinflammatory mediators including gasdermin D, caspase 1, cytokines, and chemokines. We conclude that GBP5 is required in the expression of many proinflammatory cytokines and chemokines in intestinal immune cells. In addition, GBP5 may upregulate inflammatory reactions through an inflammasome-mediated mechanism. Since GBP5 plays a proinflammatory role at the early steps of the inflammatory cascades of IBD pathogenesis, and is implicated in IBD patients of distinct genetic and environmental backgrounds, targeting GBP5 could be an effective strategy for the management of IBD.